Antecedents and consequences of social identity complexity: intergroup contact, distinctiveness threat, and outgroup attitudes. - Schmid, K; Hewstone, M; Tausch, N; Cairns, E; Hughes, J (2009)
Social identity complexity defines people's more or less complex cognitive representations of the interrelationships among their multiple ingroup identities. Being high in complexity is contingent on situational, cognitive, or motivational factors, and has positive consequences for intergroup relations. Two survey studies conducted in Northern Ireland examined the extent to which intergroup contact and distinctiveness threat act as antecedents, and outgroup attitudes as consequences, of social identity complexity. In both studies, contact was positively, and distinctiveness threat negatively, associated with complex multiple ingroup perceptions, whereas respondents with more complex identity structures also reported more favorable outgroup attitudes. Social identity complexity also mediated the effects of contact and distinctiveness threat on attitudes. This research highlights that the extent to which individuals perceive their multiple ingroups in more or less complex and differentiated ways is of central importance to understanding intergroup phenomena.